Application of imidazole as a selective inhibitor thromboxane synthetase in human platelets. - Needleman, P (1977)
Human platelet suspensions release a rabbit-aorta-contracting substance (previously identified as thromboxane A2) during aggregation produced by arachidonic acid, prostaglandin endoperoxide, thrombin, and collagen. Incubation of platelets with imidazole did not interfere with the aggregation produced by these agonists but markedly reduced the generation of the rabbit-aorta-contracting substance. We find that imidazole inhibited the conversion of exogenous or endogenous prostaglandin endoperoxide into thromboxane A2-Imidazole selectively inhibits thromboxane synthetase in intact human platelets, because this agent blocks the conversion of [14C]arachidonate into [14C]thromboxane B2 but does not inhibit the conversion of [14C]arachidonate into [14C]prostaglandin E2. The inhibition of thromboxane synthetase by imidazole is not the result of an alteration in platelet 3':5'-cyclic AMP levels. These results illustrate the utility of imidazole as a pharmacological tool and demonstrate the two unique and dissociable properties of the endoperoxides themselves--their ability to aggregate platelets and their enzymatic conversion to the potent vasoconstrictor thromboxane.